Sustainable/recyclable composites for heavy-duty vehicle floorings - Pahwa, Manmohit Singh (Cranfield University, 2020)
Composites are being increasingly used in the automotive industry to fabricate primary and secondary structural components such as tie rods, bumpers and door panels. To comply with the environmental regulations, the automotive sector is adopting sustainable composite materials and manufacturing techniques such as thermoplastic compression moulding. The switch from thermoset to thermoplastic composites to manufacture recyclable components that do not compromise performance is an examplar. As a part of this M.Sc by Research project, a critical review of components used in buses and trucks is undertaken to find a suitable component to be replaced with sustainable materials. Components like leaf springs and trailer floorings are studied to understand how significant weight reduction can be achieved using alternative materials. Recyclable and low-cost materials such as polypropylene-based composites are considered for weight reduction and improved sustainability/recyclability. The replacement of hardwood flooring in heavy-duty vehicles with relatively lighter thermoset sandwich panels is observed in the literature as an attempt to reduce weight. However, a research gap is observed in addressing the recyclability of thermoset panels which form cross-links upon curing. This thesis aims to bridge this gap by providing a lightweight alternative to wooden bus floorings while considering its cost and recyclability. Polypropylene and glass fibre-based thermoplastic sandwich panels are developed and reviewed as an alternative. These panels are manufactured using polypropylene glass fibre skins, polypropylene honeycomb and co-bonded using a thermoplastic-based hotmelt glue. The manufactured panels are found to be 1.4 kg/M²lighter than commercially available birch wood. This decrease in density equates to 51 kg of weight savings when used as a floor in a coach and potential 157 kg weight savings if the panels are used to replace the side panels. Replacing wooden floor panels with thermoplastic alternatives translates to about 1225 litres of lifetime fuel savings and a reduction of 3.4 tonnes in CO₂ emissions for a city bus with more halts. A three-point bend test is carried out to evaluate the structural performance of the fabricated sandwich panels. The bending test reveals that the manufactured thermoplastic panels show 22 MPa of bending strength. In contrast, the wooden and thermoset counterparts show a bending strength of 34 MPa and 20 MPa, respectively. Low-velocity impact tests are conducted to simulate scenarios like tool drops or hail and debris hitting the floorings. This test at 6 J of impact energy reveals significantly less residual damage when compared to thermoset counterparts.
Mills, Andrew - Associate Supervisor
Keywords: Polypropylene; Glass fibre; honeycomb; sandwich composites; thermoplastic; Bus/Coach floor panels; Trailer & Truck flooring